Worklife balance, job satisfaction, social support and employee job performance among postgraduate students in UUM - Khairani Syuhada, Abdul Rahman (2019)
As the work productivity of working adults has been increasing in recent years due to the changing of work environment and standard of living, many employee are trying their best to improve their job satisfaction and performance by continue their tertiary academic level. Hence, this study is aimed to examine the factors that affect employee job performance among postgraduate students in Universiti Utara Malaysia (UUM) and used quantitative method in order to determine the relationship between all the independent variables and dependent variable. This study assesses three key factors which act as independent variables (work life balance, job satisfaction and social support) that influence the dependent variable (employee job performance) among postgraduate students. A sample of 141 postgraduate students in Universiti Utara Malaysia (UUM) was targeted as respondents to answer the selfadministrative questionnaire. Each hypothesis was tested by using a Statistic Package for Social Science (SPSS) version 24. The research findings show that only two factors that are work life balance and job satisfaction have the significant relationship with employee job performance among postgraduate students. Some managerial implication and recommendation have been proposed at the end of this study.